Konsep Pendidikan Islam Menurut Q.S. Luqman Ayat 12-19 - Hidayat, Nurul (Institut Agama Islam Negeri (IAIN) Tulungagung, 2016)
Al-Qurâan as the main source of ethical decision in Islam providessome models of teaching, especially for children. This paper focused on educational concepts in Islam based on story of Luqman al-Hakim. According to him, Islamic educational concepts consist of Islamic monotheism, worship, amar maâruf nahi mungkar, and akhlakul karimah.